Educação de Jovens e Adultos: implicações da presença Freireana na prática pedagógica de alfabetizadores. - Silva, Jamilastreia Alves da (2007)
The present study had as objective to analyze the possible relation beetween “freirianas” conceptions that base the continued formation of the alphabetic teachers of Young and Adults in the Alphabetical Program is Citizenship, executed fot the State University of the Ceará, and pedagogical practicing of the teachers in the classroom. Characterized for a research-intervention, carried through with 5 (five) operating citizens in the alphabetical program of adults and youngs. The work was divided in three stages . In the fist one, the attainment of information concerning the previous knowledge of the ciitzens occured; in the following one the continued formation was made; and in the last one, had been carried through visits to the classrooms to observe the incorporation or not, for the alphabetical teachers, of the ideas treated during the period of formation. The results point with respect to the confirmation of the importance of the “revigoramento” of the ideas of the educator Paulo Freire in the context of the programs related to the Education of Youngs and Adults. Moreover, it has evidences of that alphabetical teachers have difficulties in accomplishing, in the pratical one, the “freirianas” ideas studied in the formation meetings. Although to be unanimous in affirming its importance for the success of the pedagogical action, obstacles to the attemp exist to breach with the traditional education, based in the monolog and the repetition. The lack of theoretician-practical basement of the alphabetical teachers, exactly having all these already participated of some qualifications offered in the scope of the Program, deserves greaters reflections. The constatation of clear changes in the attitude of the alphabetical teachers, after the formation meetings, indicates that the adopted boarding and the methodology in the intervention bring contribution accomplish to the continued formation of the teachers